Government budgeting and expenditure control theory and practice - Premchand, A. (International Monetary Fund, 1983)
This book offers a comprehensive review of fiscal policies and their implications for budgeting and expenditure controls. It provides an in-depth discussion of techniques, proceedings, and processes of budgeting with illustrative material drawn from the experiencs of industrial and developing countries.